Cu / ZnO composite material with three-dimensional ordered macroporous and hollow wall structure as well as preparation method and application of Cu / ZnO composite material
By using a Cu/ZnO composite catalyst with three-dimensional ordered macropores and hollow wall structure, combined with the photothermal synergistic effect, the problems of high energy consumption and easy catalyst deactivation in the prior art are solved, and the effect of efficient hydrogen production at low temperatures is achieved.
Patent Information
- Application Number
- CN202510092714.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing photocatalytic and thermal catalysis technologies have problems such as high energy consumption, high cost, easy deactivation of catalyst active sites, and low photogenerated carrier transfer efficiency in hydrogen storage and transportation.
The Cu/ZnO composite catalyst with three-dimensional ordered macropores and hollow wall structure was prepared by the template method, and the photothermal synergistic effect was used to produce hydrogen efficiently at low temperatures.
It achieves efficient hydrogen production at low temperatures (100-130°C), reduces energy consumption, improves the stability and conversion efficiency of the catalyst, and solves the problem of catalysts being easily deactivated at high temperatures in traditional technology.
Smart Images

Figure CN119909689A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal organic framework materials, and in particular to a Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure, and a preparation method and application thereof. Background Art
[0002] In recent decades, with the use of fossil fuels, environmental pollution and energy resource depletion have become increasingly serious, and there is an urgent need to find other types of alternative energy. Hydrogen, as an energy option with sustainable development characteristics and environmental friendliness, has attracted widespread attention. However, the storage and transportation of hydrogen has become a bottleneck restricting its widespread application. Methanol (CH3OH), as a safe, economical and easy-to-store liquid organic hydrogen carrier with a high H2 capacity (12.6wt%), is regarded as an ideal solution to the storage and transportation challenges in hydrogen energy utilization.
[0003] The traditional mode of thermal catalytic methanol liquid phase reforming hydrogen production (APRM) has reached the industrial and market requirements in terms of hydrogen production and hydrogen purity, but this technology generally requires high temperatures of 190°C to 300°C in the thermal catalytic process to achieve efficient hydrogen generation, which is energy-intensive and costly. In contrast, solar photocatalytic conversion technology promotes the activation of methanol through the interaction between photogenerated carriers and substrates, thereby greatly reducing the activation energy of the reaction, allowing efficient hydrogen production at lower temperatures or even room temperature; however, the current photocatalytic system has limited energy output, low conversion efficiency, low transfer efficiency of photogenerated carriers, and high recombination rate, and its advantages are not prominent.
[0004] Moreover, in photothermal catalytic technology, catalysts play a vital role. They are not only the core to promote chemical reactions, but also the key to determine the performance of the entire system. At present, the catalysts of the photocatalytic system mainly include titanium dioxide (TiO2), cadmium sulfide (CdS), zinc oxide (ZnO), etc. These materials can drive the redox reactions of organic substances such as methanol. However, although these catalysts have shown certain photocatalytic activity, they still face many challenges in practical applications, such as the active sites in the catalysts are easily deactivated at high temperatures, the energy consumption of hydrogen production is high, the separation and transmission efficiency of photogenerated carriers is low, and the stability needs to be improved. Further improvement is still needed. Summary of the invention
[0005] The purpose of the present invention is to provide a Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure and its preparation method and application to solve the above-mentioned problems in the background technology. The Cu / ZnO composite material prepared by the present invention has a unique hollow / macroporous structure and a large specific surface area, which is conducive to the exposure of the active metal Cu sites therein, can promote contact and activation with reactants, and can achieve the technical effect of efficient hydrogen production at low temperature (100-130°C).
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a Cu / ZnO composite material having a three-dimensional ordered macropore and a hollow wall structure, comprising the following steps:
[0008] The template is immersed in a ZIF-8 precursor solution and allowed to stand to obtain a precursor A;
[0009] The precursor A and the copper source are mixed in a solvent and reacted to obtain a precursor B;
[0010] The precursor B is calcined and then thermally reduced to obtain a Cu / ZnO composite material catalyst with three-dimensional ordered macropores and hollow wall structures.
[0011] Preferably, the standing time is 1 hour.
[0012] Preferably, the solvent is ethanol.
[0013] Preferably, after the reaction is completed, the steps of filtering, washing and drying are further included.
[0014] Preferably, the ZIF-8 precursor solution contains dimethylimidazole and zinc salt.
[0015] More preferably, the method for preparing the ZIF-8 precursor solution comprises the following steps: preparing a dimethylimidazole ligand solution and a zinc salt solution, ultrasonicating them in a beaker for 20 minutes respectively, and then mixing and standing the mixture to obtain the ZIF-8 precursor solution.
[0016] Conventional zinc salts in the art can be used in the present invention. Preferably, the zinc salt is zinc nitrate and / or zinc acetate; more preferably, the mass ratio of dimethylimidazole to zinc nitrate is 1:0.55-0.75.
[0017] Preferably, the template is a three-dimensional ordered polystyrene sphere template, and the average particle diameter is 180-250 nm.
[0018] Preferably, the preparation method of the three-dimensional ordered polystyrene sphere template comprises the following steps: 65 mL of styrene is thoroughly washed with 20 mL of 10% NaOH solution and deionized water in sequence to remove the stabilizer therein; the washed styrene is added to a three-necked round-bottom flask, and 500 mL of an aqueous solution containing 2.5 g of PVP is added, and then the polymerization reaction of styrene is initiated, and magnetic stirring is performed at 90° C. for 24 hours and then cooled to obtain emulsion-like monodisperse colloidal polystyrene spheres, which are treated by filtering or centrifugation at a rotation speed of 10,000 rpm, and then dried to obtain a three-dimensional ordered PS template.
[0019] Conventional copper sources in the art can be used in the present invention. Exemplarily, the copper source is copper nitrate and / or copper acetate; preferably, the mass ratio of the precursor A to the copper source is 1:1.5-3.5.
[0020] Preferably, the reaction is carried out under stirring conditions, the stirring speed is 300-400 rpm, and the time is 30-50 min.
[0021] Preferably, the calcination treatment is carried out at a temperature of 450-550° C., a heating rate of 5° C. / min, a time of 3 hours, and an atmosphere of air.
[0022] More preferably, the calcination temperature is 500°C.
[0023] Preferably, the thermal reduction treatment is carried out at a temperature of 300° C., a heating rate of 5° C. / min, a time of 1 h, and a hydrogen atmosphere.
[0024] The second technical solution of the present invention is to provide a Cu / ZnO composite material having three-dimensional ordered macropores and hollow wall structure obtained according to the above preparation method.
[0025] The third technical solution of the present invention is to provide an application of the above-mentioned Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure in the field of hydrogen production by photothermal catalytic liquid phase reforming of methanol.
[0026] The present invention reduces the energy consumption in the reaction process by means of the photothermal coupling synergistic effect, and uses the energy provided by sunlight to provide a driving force for the reaction. Therefore, the catalytic activity can be maintained even at low temperatures, thereby achieving low-energy consumption and stable hydrogen production at low temperatures.
[0027] Technical solution 4 of the present invention: Provided is a method for producing hydrogen by photothermal catalytic liquid phase reforming of methanol, comprising the following steps:
[0028] The Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure, methanol, water and alkali are mixed and reacted to obtain hydrogen.
[0029] Preferably, the base is potassium hydroxide (KOH); the molar ratio of methanol to water is 1:1-3; the reaction is carried out under anaerobic, light and heating conditions, and the heating temperature is 100-210°C.
[0030] The technical principles of the present invention are as follows:
[0031] Since the existing catalysts with active metal Cu loaded organic skeleton material structure have the problem that the active metal Cu is easy to fall off and aggregate on the organic skeleton, which easily leads to a reduction in active sites, easy recombination of photogenerated electrons and holes, and unstable hydrogen production catalytic activity, the present invention provides a Cu / ZnO composite material catalyst with three-dimensional ordered macropores and hollow wall structure; the material stably encapsulates Cu nanoparticles in a three-dimensional ordered ZnO skeleton, effectively alleviates the aggregation of Cu nanoparticles, is beneficial to the migration of photogenerated carriers, solves the problem of low migration efficiency of photogenerated electrons and holes under photocatalysis, and can more effectively utilize sunlight at low temperatures.
[0032] The catalyst is prepared by a two-step pyrolysis reduction strategy involving a metal organic framework (MOF). First, the present invention prepares a three-dimensional ordered polystyrene (PS) sphere template, and then fills the gaps of the template with a ZIF-8 precursor solution, thereby promoting the crystallization of MOF in the template; finally, a two-step annealing treatment is performed in air and hydrogen atmospheres in turn, and the prepared Cu / ZnO composite catalyst has an ordered macropore and hollow wall structure, a large number of exposed intrinsic active sites, which is conducive to the transfer of photogenerated electron-hole pairs, accelerates the catalytic conversion of substances adsorbed on the catalyst surface, and shows excellent photothermal catalytic methanol aqueous phase reforming hydrogen production performance.
[0033] The beneficial technical effects of the present invention are as follows:
[0034] The Cu / ZnO composite material prepared by the present invention has a unique hollow / macroporous structure and a large specific surface area, which is conducive to the exposure of the active metal Cu sites therein and can promote contact and activation with reactants. In addition, the voids inside the hollow structure enhance the scattering of incident light and enhance the utilization rate of sunlight. The Cu nanoparticles therein, as the active center of photothermal catalysis, are effectively dispersed in the macropores of the three-dimensional ordered ZnO, effectively avoiding the aggregation between the metal sites and facilitating the migration of photogenerated carriers.
[0035] The Cu / ZnO composite catalyst with three-dimensional ordered macropores and hollow wall structure of the present invention can combine thermal energy and solar energy, realize photothermal synergistic effect, accelerate the catalytic conversion process of the adsorbed matrix on the catalyst surface, and can well solve the problems of low conversion efficiency of existing photocatalytic schemes and easy deactivation of catalysts at high temperatures in thermal catalytic schemes. At the same time, by utilizing the activation effect of sunlight, the technical effect of efficient hydrogen production at low temperature (100-130°C) can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 1 is the XRD spectrum of ZIF-8, CuO / ZnO and Cu / ZnO composite catalysts in Example 1.
[0038] Figure 2 The scanning electron microscope images of ZIF-8 and Cu / ZnO composite catalysts in Example 1. Among them, (a) is ZIF-8, and (b) is Cu / ZnO composite catalyst.
[0039] Figure 3 This is a comparison chart of the photothermal catalytic methanol liquid phase hydrogen production performance of ZIF-8 and Cu / ZnO composite catalysts in Example 1.
[0040] Figure 4 This is a performance diagram of the photothermal catalytic methanol liquid phase hydrogen production at low temperature of the Cu / ZnO composite catalyst in Example 1. DETAILED DESCRIPTION
[0041] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0042] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0045] The performance of the photocatalytic system depends largely on the intrinsic activity of the catalyst and the accessible active sites. For the former factor, various noble metal (Pd, Ru and Pt) and non-noble metal (Cu and Ni) catalysts have been studied for catalytic reactions; among them, copper-based active sites have the characteristics of high activity, selectivity and affordability in the product system of the present invention, so copper-based catalysts are selected as the research object. For the latter factor, the catalyst structure with a large specific surface area is conducive to the exposure of the active metal Cu site, which can promote contact and activation with the reactants; in addition, the voids inside the hollow structure will enhance the scattering of the incident light and enhance the utilization of sunlight.
[0046] At present, metal organic frameworks (MOFs) have been identified as highly adaptable precursors or templates. Metal compounds derived from MOFs can inherit the initial morphology, size and structure of MOF precursors well through reasonable pyrolysis conditions; during the pyrolysis treatment process of the present invention, the decomposition of organic ligands and the formation of hybrid pore walls in MOFs limit the aggregation of metal clusters and enhance mechanical flexibility. The ZnO material prepared by pyrolysis of three-dimensional ordered macroporous ZIFs in the present invention not only exhibits an interconnected ordered macroporous structure, providing a rapid transmission channel for reactants, but also increases the contact surface area of reactants, thereby enhancing the diffusion kinetics of substances, and can combine the advantages of the two, fully expose active sites, and significantly improve the performance of photothermal catalytic methanol liquid phase reforming hydrogen production reaction. The present invention overcomes the problem of rapid recombination of photoelectron-hole pairs in traditional photocatalysts, and achieves efficient and stable hydrogen production at low cost.
[0047] The "room temperature" in the present invention is 10-30°C unless otherwise specified.
[0048] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0049] Example 1
[0050] A method for preparing a Cu / ZnO composite catalyst, the specific steps are as follows:
[0051] 1. Preparation of ZIF-8
[0052] 65 mL of styrene was thoroughly washed with 20 mL of 10% NaOH solution and deionized water in sequence to remove the stabilizer; 65 mL of washed styrene was added to a three-necked round-bottom flask, and 500 mL of an aqueous solution containing 2.5 g of PVP was added, and the mixture was stirred at 90° C. for 24 h and then cooled to initiate the polymerization reaction of styrene to obtain milky monodisperse colloidal polystyrene spheres, which were then filtered to form a three-dimensional ordered PS template with a monodisperse particle diameter of about 210 nm;
[0053] 8.15 g Zn(NO3)2·6H2O and 3.47 g 2-methylimidazole (the mass ratio of dimethylimidazole to zinc nitrate is 1:0.65) were dissolved in 45 mL of methanol solution to obtain a ZIF-8 precursor solution; the PS template was placed in the above ZIF-8 precursor solution and soaked for 1 hour so that the gaps between the three-dimensional colloidal spheres were completely filled with the precursor solution, and then the reaction system was transferred to a beaker and dried at 60°C for 12 hours to promote crystallization and then thoroughly washed with DMF and methanol to obtain ZIF-8.
[0054] 2. Preparation of Cu / ZIF-8
[0055] Cu(NO3)2·3H2O was dissolved in 30 mL of ethanol and stirred for 5 minutes, and then the above-mentioned ZIF-8 was added (the mass ratio of ZIF-8 and Cu(NO3)2·3H2O was 1:2.5), and stirred at a stirring speed of 9000 rpm for 30 minutes. Then, the light blue solid was separated by centrifugation, washed thoroughly with methanol, and vacuum dried at 60°C overnight to obtain Cu / ZIF-8.
[0056] 3. Preparation of Cu / ZnO composite catalyst
[0057] The Cu / ZIF-8 was calcined in air (calcination temperature was 500°C, heating rate was 5°C / min, time was 3h) to obtain CuO / ZnO, and then placed in hydrogen atmosphere for thermal reduction treatment (thermal reduction temperature was 300°C, heating rate was 5°C / min, time was 1h) to obtain Cu / ZnO composite catalyst. After testing, the mass proportion of Cu in the product was 8.1%.
[0058] Example 2
[0059] The only difference from Example 1 is that the mass ratio of dimethylimidazole to zinc nitrate is changed to 1:0.55 by changing the amount of dimethylimidazole added. After testing, the mass proportion of Cu in the product is 7.7%.
[0060] Example 3
[0061] The only difference from Example 1 is that the mass ratio of dimethylimidazole to zinc nitrate is changed to 1:0.75 by changing the amount of dimethylimidazole added. After testing, the mass proportion of Cu in the product is 8.3%.
[0062] Example 4
[0063] The only difference from Example 1 is that the mass ratio of ZIF-8 to Cu(NO3)2·3H2O is changed to 1:1.5 by modifying the amount of Cu(NO3)2·3H2O added. After testing, the mass proportion of Cu in the product is 5.4%.
[0064] Example 5
[0065] The only difference from Example 1 is that the mass ratio of ZIF-8 to Cu(NO3)2·3H2O is changed to 1:3.5 by modifying the amount of Cu(NO3)2·3H2O added. After testing, the mass proportion of Cu in the product is 9.4%.
[0066] Example 6
[0067] The only difference from Example 1 is that Cu(NO3)2·3H2O is replaced by an equal mass of copper acetate. After testing, the mass proportion of Cu in the product is 3.2%.
[0068] Example 7
[0069] The only difference from Example 1 is that the calcination temperature is changed to 450° C. After testing, the mass proportion of Cu in the product is 7.7%.
[0070] Example 8
[0071] The only difference from Example 1 is that the calcination temperature is changed to 550° C. After testing, the mass proportion of Cu in the product is 8.1%.
[0072] Comparative Example 1
[0073] The only difference from Example 1 is that ZIF-8 in step 2 is replaced by ZIF-67 precursor solution, and the mass ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O in the ZIF-67 precursor solution is 2.5:1; wherein the preparation method of the ZIF-67 precursor solution is as follows:
[0074] 1) Dissolve 5.82 g Co(NO3)2·6H2O and 6.16 g dimethylimidazole in 150 mL methanol to form two transparent solutions. Then pour the dimethylimidazole solution into the Co(NO3)2·6H2O solution and stir at room temperature for 24 h to obtain the ZIF-67 precursor solution.
[0075] Comparative Example 2
[0076] The only difference from Example 1 is that ZIF-8 in step 2 is replaced by MIL-125 (Ti) precursor solution, and the mass ratio of Cu (NO3) 2·3H2O to butyl titanate in the MIL-125 (Ti) precursor solution is 2.5:1; wherein the preparation method of MIL-125 (Ti) is as follows:
[0077] 1) 1.56 mL (4.5 mmol) of butyl titanate was added dropwise to 3 g (18 mmol) of terephthalic acid, N,N-dimethylformamide (54 mL) and anhydrous methanol (6 mL) were mixed and added to the above sample, stirred at room temperature for 1 hour to form a white turbid uniform liquid, which was then transferred to a 100 mL autoclave and placed in a 160° C. forced drying oven for high pressure reaction for 20 hours.
[0078] 2) The solid obtained in 1) after the centrifugal treatment is washed three times with DMF and anhydrous methanol respectively, dried and dissolved in methanol to obtain a precursor solution.
[0079] Comparative Example 3
[0080] The only difference from Example 1 is that the ZIF-8 in step 2 is replaced by ordinary ZIF-8 of the same mass; wherein the preparation method of ordinary ZIF-8 is as follows:
[0081] 1) Dissolve Zn(NO3)2·6H2O and 2-methylimidazole (the molar ratio of dimethylimidazole to zinc nitrate is 1:8) in methanol respectively, mix and stir at room temperature for 10 h;
[0082] 2) The solid obtained in 1) after the centrifugal treatment was washed three times with methanol by centrifugation and dried at 50°C.
[0083] Effect verification
[0084] 1. The Cu / ZnO composite catalysts prepared in Examples 1 to 8 were characterized and their photothermal catalytic performance was tested.
[0085] The crystal structure of the product of Example 1 was analyzed by X-ray diffractometer.
[0086] Figure 1 1 is the XRD spectrum of ZIF-8, CuO / ZnO and Cu / ZnO composite catalysts in Example 1.
[0087] Figure 1In the figure, a represents the XRD pattern of ZIF-8, b represents the XRD pattern of CuO / ZnO, and c represents the XRD pattern of Cu / ZnO composite catalyst.
[0088] from Figure 1 It can be seen that ZIF-8, CuO / ZnO and Cu / ZnO composite materials all have good crystallinity; the characteristic peaks of CuO and ZnO can be observed in the XRD diffraction pattern of CuO / ZnO, indicating that ZIF-8 is successfully calcined into ZnO and Cu is successfully encapsulated; the CuO peak disappears and the Cu peak appears in the XRD pattern of the Cu / ZnO composite catalyst, indicating that Cu in the Cu / ZnO composite material is successfully reduced to a zero-valent state and the catalyst has been successfully prepared. The XRD patterns of CuO / ZnO and the final product in Examples 2 to 8 are basically consistent with those in Example 1.
[0089] Figure 2 The scanning electron microscope images of ZIF-8 and Cu / ZnO composite catalysts in Example 1. Among them, (a) is ZIF-8, and (b) is Cu / ZnO composite catalyst.
[0090] from Figure 2 As shown in (a), the prepared ZIF-8 has a three-dimensional ordered structure. After the introduction of highly active Cu nanoparticles, the main three-dimensional porous structure of the Cu / ZnO composite material in (b) did not collapse, and the surface was relatively rough, indicating that the organic ligand was successfully converted into a porous zinc oxide material without obvious structural collapse or thermal stress shrinkage. The SEM images of the products of Examples 2 to 8 are basically consistent with those of Example 1, and the structure of the Cu / ZnO composite material is basically unchanged.
[0091] 2. ZIF-8 and Cu / ZnO composite materials were tested for hydrogen production by photothermal catalytic liquid phase reforming of methanol.
[0092] Photothermal catalytic methanol liquid phase reforming to produce hydrogen is carried out in a photothermal reactor and heated by a heating furnace equipped with a magnetic stirring device. The specific test method is as follows:
[0093] The photothermal catalytic methanol liquid phase hydrogen production reaction was carried out in a stainless steel high-pressure photothermal autoclave (CEL-HPR50, 50mL) with a quartz lining, a magnetic stirrer and a visible sapphire window. Under the optimal reaction conditions, the Cu / ZnO composite catalyst was activated at 150°C under vacuum and then transferred to the photothermal reactor lining containing 10mL MeOH / H2O mixed solution (nMeOH / nH2O=1) and 5wt% KOH; the sealed reactor was repeatedly filled and discharged with 2MPaN2 three times, and then reacted at 210°C for 80min under 2MPaN2 atmosphere, irradiation with a 300W Xe lamp (CEL-HXF300-T3) and a stirring speed of 500rpm. After the reaction, the gas products in the headspace of the autoclave were analyzed by GC chromatography to determine the amount of H2 produced and compared with the relevant data under no light conditions. The test results are shown in Figure 3 As shown in Table 1. By adjusting the above reaction temperature, the hydrogen production performance of the product at low temperature (100-210°C) was tested. The test results are shown in Figure 4 shown.
[0094] Figure 3 This is a comparison chart of the photothermal catalytic methanol liquid phase hydrogen production performance of ZIF-8 and Cu / ZnO composite catalysts in Example 1.
[0095] Figure 3 The results show that the photothermal hydrogen production rate of the original ZIF-8 is about 5 times that of pure thermal hydrogen production, indicating that the reaction is mainly a light-to-heat promotion reaction; it can also be observed that the hydrogen production performance of the Cu / ZnO composite material under the photothermal effect reaches 124mmol·g -1 ·h -1 , which is 13.1 times the pure thermal hydrogen production rate and 7.52 times that of ZIF-8. This is mainly because the photothermal effect can promote each other. Light can accelerate the transfer of electrons by exciting the generation of photogenerated carriers; heating can significantly accelerate the reaction rate by accelerating the migration rate of photogenerated carriers. Cu / ZnO composites introduce Cu nanoparticles into the skeleton, which can encapsulate highly active and easily inactivated active sites in the framework of MOF, highly disperse active metals, prolong the life of electron-hole pairs, and facilitate the transfer of energy and electrons between active sites and carrier MOF. At the same time, Cu nanoparticles are active sites for hydrogen production from methanol reforming under thermal catalysis, and have been proven to have excellent photoelectric properties. Under light, the activation energy of the substrate methanol water can be effectively reduced, allowing it to react at low temperatures; the combination of the two can greatly increase the surface active sites, which is very beneficial for increasing the life and migration rate of electrons and holes. This shows that the photothermal catalytic methanol hydrogen production performance of Cu / ZnO composite catalysts with three-dimensional ordered macropores and hollow wall structures can indeed be significantly improved.
[0096] Figure 4 This is a performance diagram of the photothermal catalytic methanol liquid phase hydrogen production at low temperature of the Cu / ZnO composite catalyst in Example 1.
[0097] Table 1 Photothermal catalytic methanol liquid phase reforming hydrogen production test performance data of ZIF-8 in Example 1, and the products of Examples 1 to 8 and Comparative Examples 1 to 3
[0098]
[0099] The above experimental results show that the Cu / ZnO composite material prepared by the present invention has a unique hollow / macroporous structure and a large specific surface area, which is conducive to the exposure of the active metal Cu sites therein and can promote contact and activation with the reactants. In addition, the voids inside its hollow structure will enhance the scattering of the incident light and enhance the utilization rate of sunlight. The Cu nanoparticles therein, as the active center of photothermal catalysis, are effectively dispersed in the macropores of the three-dimensional ordered ZnO, effectively avoiding the aggregation between the metal sites, which is conducive to the migration of photogenerated carriers. The Cu / ZnO composite catalyst with three-dimensional ordered macropores and hollow wall structure of the present invention can combine thermal energy and solar energy, realize the photothermal synergistic effect, accelerate the catalytic conversion process of the adsorption matrix on the catalyst surface, and can well solve the problem of low conversion efficiency of the existing photocatalytic scheme and easy deactivation of the catalyst in the thermal catalytic scheme at high temperature. At the same time, the activation effect of sunlight can be used to achieve the technical effect of efficient hydrogen production at low temperature (100-130°C).
[0100] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a Cu / ZnO composite material having three-dimensional ordered macropores and a hollow wall structure, characterized in that: The following steps are involved: The template is immersed in a ZIF-8 precursor solution and allowed to stand to obtain a precursor A; The precursor A and the copper source are mixed in a solvent and reacted to obtain a precursor B; The precursor B is calcined and then thermally reduced to obtain a Cu / ZnO composite material catalyst with three-dimensional ordered macropores and hollow wall structures.
2. The preparation method according to claim 1, characterized in that: The ZIF-8 precursor solution contains dimethylimidazole and zinc salt.
3. The preparation method according to claim 1, characterized in that: The template is a three-dimensional ordered polystyrene sphere template, and the average particle diameter is 180-250nm.
4. The preparation method according to claim 1, characterized in that: The copper source is copper nitrate and / or copper acetate; the mass ratio of the precursor A to the copper source is 1:1.5-3.
5.
5. The preparation method according to claim 1, characterized in that: The reaction is carried out under stirring conditions, the stirring speed is 300-400 rpm, and the time is 30-50 min.
6. The preparation method according to claim 1, characterized in that: The calcination treatment is carried out at a temperature of 450-550° C., a heating rate of 5° C. / min, a calcination time of 3 hours, and an air atmosphere.
7. The preparation method according to claim 1, characterized in that: The thermal reduction treatment was carried out at a temperature of 300° C., a heating rate of 5° C. / min, a time of 1 h, and a hydrogen atmosphere.
8. A Cu / ZnO composite material having three-dimensional ordered macropores and hollow wall structure obtained according to the preparation method according to any one of claims 1 to 7.
9. Use of the Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure as claimed in claim 8 in the field of hydrogen production by photothermal catalytic liquid phase reforming of methanol.
10. A method for producing hydrogen by photothermal catalytic methanol liquid phase reforming, characterized in that: The following steps are involved: The Cu / ZnO composite material with three-dimensional ordered macropores and hollow wall structure as claimed in claim 8, methanol, water and alkali are mixed and reacted to obtain hydrogen.
Citation Information
Cited By
Boron-containing copper-based three-dimensional metal organic framework material as well as preparation method and application thereof
CN120329565A